2000
DOI: 10.1038/labinvest.3780130
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction in Congenital Nephrotic Syndrome

Abstract: SUMMARY:The molecular mechanisms maintaining the kidney glomerular filtration barrier remain poorly understood. Recent evidence suggests that mitochondrial dysfunction is a characteristic feature of kidney glomeruli in congenital nephrotic syndrome of the Finnish type (CNF). Here we searched for detailed functional evidence of mitochondrial lesion in CNF kidneys. We used histochemical and immunohistochemical methods, quantitative measurement of mitochondrial DNA, and superoxide production to characterize the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…This finding is of clinical relevance to human glomerular disease. For example, Solin et al 43 reported that a reduction in mtDNA copy number in the kidney cortex accounts for MtD in Finnish type congenital nephrotic syndrome. Holthofer et al 44 also reported down-regulation of the mitochondrially encoded respiratory chain complex in glomeruli isolated from the same patients.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is of clinical relevance to human glomerular disease. For example, Solin et al 43 reported that a reduction in mtDNA copy number in the kidney cortex accounts for MtD in Finnish type congenital nephrotic syndrome. Holthofer et al 44 also reported down-regulation of the mitochondrially encoded respiratory chain complex in glomeruli isolated from the same patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction and altered mitochondrial gene expression have also been documented in patients with NS secondary to nephrin mutations, 33,34 suggesting that, regardless of the initial insult, mitochondria play an important role in podocyte metabolism and may be actively involved in the pathophysiology of various forms of NS.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies revealed altered expression of mitochondrial genes and mitochondrial dysfunction in acquired and congenital human nephrotic syndrome (3,4). Furthermore, collapsing FSGS has been associated with mitochondrial injury with inherited mutations in genes encoding for mitochondrial function (5).…”
Section: Introductionmentioning
confidence: 99%